Variability in chlorophyll fluorescence spectra of eggplant fruit grown under different light environments: A case study - Ospina Calvo, Brian (2017)
The main goal of the present work was to clarify physiological strategies in plants whose chloroplasts were developed under different light environments. The specific objective was to elucidate the influence of the spectral distribution of light on the chlorophyll fluorescence ratio and on photosynthetic parameters. To achieve this purpose, three species of eggplant fruit (black, purple and white striped and white) were used as a case study and their chlorophyll fluorescence was analyzed in detail. Spectra of the non-variable fluorescence in each part of the fruit were corrected for distortions by light reabsorption processes using a physical model. The main conclusion of this work was that the corrected fluorescence ratio was dependent on the contribution of each photosystem to the fluorescence and consequently on the environmental lighting conditions, becoming higher when illumination was rich in long wavelengths. Variable chlorophyll fluorescence, similar to that observed from plant leaves, was detected for the pulp of the black eggplant, for the pulp of the purple and white striped eggplant and for the intact fruit of the black eggplant. The maximum quantum efficiency of photosystem II in the light-adapted state (F′v/F′m), the quantum efficiency of photosystem II (ΦPSII), and the photochemical and non-photochemical quenching coefficients (qP and qNP/NPQ respectively) were determined in each case. The results could be explained very interestingly, in relation with the proportion of exciting light reaching each photosystem (I and II). The photochemical parameters obtained from variable chlorophyll fluorescence, allowed us to monitor non-destructively the physiological state of the black fruit during storage under both chilled or room-temperature conditions.